PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA GURU SEKOLAH MINGGU BUDDHA (SMB) CHONG-DE SE-SUMATERA UTARA - Ika Kartika; Muljadi; Isomudin (Dhammavicaya : Jurnal Pengkajian Dhamma, 2022)
The purpose of this study was to determine the effect of compensation and work discipline on the performance of Chong-De Buddhist Sunday School (SMB) teachers throughout North Sumatra. This study uses multiple regression analysis. In this study the determination of the sample using probability sampling technique with the number of samples used in this study as many as 86 respondents. This study uses primary data, data is collected by distributing questionnaires to respondents via google forms. Testing the research hypothesis using SPSS 20.0 for Windows.With the coefficient ry12 = 0.917, the coefficient of determination (ry12)2 = 0.840 (84.0%) with the regression equation Y=34,805 + 0.165 X1 + 0.682 X2. This means that the higher the compensation and work discipline together, it can improve the teacher's performance of the Chong-De Buddhist Sunday School (SMB) teachers in North Sumatra. Work discipline has a positive effect on teacher performance Buddhist Sunday School (SMB) Chong-De, North Sumatra. Compensation and work discipline have a positive and significant effect together on the performance of teachers Buddhist Sunday School (SMB) Chong-De, North Sumatra. The regression equation in this study is as follows: Y1,2 = 34.805 + 0.165X1 + 0.682X2.Based on these results, in order to optimize teacher performance, policies and regulations are needed to increase compensation and work discipline.